Implementasi Kebijakan Pendidikan di MTs PAB 2 Sampali - Ahmad Mukhlasin; Clara Tri Putri; Fikri Syuhadi; Pitri Ristia Ningsih; Sari Bulan Hasibuan (Jurnal Bintang Pendidikan Indonesia, 2024)
This research discusses the planning, implementation and evaluation of educational policies at MTs PAB 2 Sampali as an integral part of efforts to improve the quality of secondary education. Qualitative methods were used with interviews, observation and document analysis. Madrasa heads were the main respondents, ensuring an in-depth understanding of the dynamics of policy implementation. 1) Policy planning begins with identifying needs and challenges involving analysis of student achievement, facilities and curriculum development. Consultation and participation of stakeholders, including teachers, parents and students, is the next step. Goals and objectives are set with a focus on improving achievement, strengthening the curriculum, and student participation. 2) The implementation process begins with careful planning, communication and socialization of policies to stakeholders, training and professional development for teachers, full implementation of policies, and ongoing evaluation. Positive impacts can be seen in increasing student achievement, student participation in extracurricular activities, and parental involvement. However, limited resources and resistance to change are challenges that need to be overcome. 3) This research provides a positive picture of MTs PAB 2 Sampali's efforts to improve the quality of education through policy planning, implementation and evaluation. Even though challenges exist, a commitment to continuous improvement can make this institution an inspiring example in planning education policies that have a positive impact.